Challenges of Wireless Sensor Networks and their Solutions - Leena Obaid; Roba Alhashmiy; Shahad Alsulami; Atheer Majed; Abdul Ahad Siddiqi (المجلة الدولية للحاسبات والمعلوماتية, 2024)
Wireless Sensor Networks (WSNs) have emerged as a critical technology with uses in the fields of smart cities, industrial automation, healthcare, and environmental monitoring. This research paper provides a thorough review of the challenges inherent in WSNs, with the intention of providing light on the challenges that practitioners and researchers have while setting up and maintaining these networks. The challenges involve several aspects, comprising data management, security, scalability, energy efficiency, and dependability. Security concerns: given that these networks’ communication is open and wireless, maintaining data integrity and secrecy presents substantial issues. Furthermore, it is essential to guarantee data transmission dependability in dynamic, frequently severe situations. This research analyzes these challenges, looks at the methods and solutions that are currently being offered in the literature, and also points out areas that need more research and development in the area of wireless sensor networks. Comprehending and resolving these obstacles is essential to realizing WSNs’ complete potential and promoting their extensive integration in various fields.